PEMBERDAYAAN MASYARAKAT SEKOLAH MELALUI SOSIALISASI PESAN MAKAN SAYUR DAN BUAH PADA ANAK USIA PRASEKOLAH - Mulyani, Erry Yudhya; Jusat, Idrus (Universitas Esa Unggul, 2016)
AbstractHealthy Eating Patterns with a Balanced Nutrition is one of the main factors in the complexity of nutritional problems in Indonesia. Education and counseling on health and nutrition to the community is not an easy, itâs because of concerns to behavioral changes. RISKESDAS 2010 data showed the nutritional status based on weight for age and weight for height in Jakarta were 10.1% (obese) and 10.8% (underweight), respectively. Based on the nutritional status indicator BMI for age in DKI Jakarta had a prevalence of 12.8% of obese and 6.5% for underweight. The purpose of this activity was to Empower Community at Schools through by socialization messages of eating vegetables and fruit in pre-school children, in an effort to improve the knowledge, attitudes, and behaviors about eating vegetables and fruit at TK Pelita Hati, Villa Dago Tol, Serua-Ciputat. The method used was a cross-sectional design. The target in this activity is the pre-school age children at KB / TK Pelita Hati. The total number of sample were 65 students from play group to grade at TK A and B. The results showed that the description of childrenâs knowledge about food sources 26.60 Â± 7.17 and the knowledge about balanced nutrition was 36.40 Â± 10.05. Based on the observations showed that most of the children were enthusiastic to answer the open questions about fruits and vegetable material provided by counselor and the media helpfully the children to ask and discuss with the counselor. Therefore, it is necessary to do activities that are more intensive socialization and students interest to establish a behavior healthy eating pattern with a balanced nutrition.Keywords: balanced nutrition, fruits and vegetables, preschools childrenÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â AbstrakPola Makan dengan Gizi Seimbang merupakan salah satu faktor utama pada kompleksnya permasalahan gizi di Indonesia. Pendidikan dan penyuluhan tentang kesehatan dan gizi kepada masyarakat bukan merupakan hal yang mudah oleh karena menyangkut perubahan perilaku. Menurut data RISKESDAS 2010 Status Gizi BB/U dan BB/TB DKI Jakarta memiliki status gizi gemuk 10,1% dan Kurus 10,8%. Berdasarkan Status gizi IMT/U DKI Jakarta memiliki prevalensi 12,8 % untuk kategori gemuk dan 6,5% untuk kategori kurus. Tujuan dari kegiatan ini adalah untuk Memberdayakan Masyarakat Sekolah melalui Sosialisasi pesan makan sayur dan buah pada anak prasekolah dalam upaya peningkatan pengetahuan, sikap, dan perilaku tentang makan sayur dan buah di TK Pelita Hati, Villa Dago Tol, Serua-Ciputat. Metode yang digunakan adalah cross-sectional design. Sasaran dalam kegiatan ini adalah anak-anak usia prasekolah di KB/TK Pelita Hati yang berjumlah 65 siswa mulai dari kelompok bermain sampai dengan kelas TK A dan B. Dari hasil pengabdian didapat gambaran pengetahuan anak tentang sumber makanan 26.60 Â± 7.17 dan pengetahuan tentang gizi seimbang sebesar 36.40 Â± 10.05. Berdasarkan hasil observasi didapat bahwa dari penyuluhan yang diberikan tentang sayur dan buah hampir sebagian besar anak antusias dalam menjawab pertanyaan terbuka yang diberikan oleh penyuluh dan dari media yang digunakan dapat menstimulasi anak untuk banyak bertanya serta berdiskusi dengan para penyuluh. Oleh karenanya, perlu dilakukan kegiatan yang sosialisasi yang lebih intensif dan menarik para siswa untuk dapat membentuk pola perilaku sehat bergizi seimbang.Kata Kunci: gizi seimbang, sayur dan buah, anak prasekolah